PENGARUH SUPPORTIVE WORK ENVIRONMENT (SWE) TERHADAP RETENSI KARYAWAN YANG DIMEDIASI OLEH KOMITMEN AFEKTIF PADA KARYAWAN KYRIAD MURAYA HOTEL BANDA ACEH - Suci Alifa; Lenny Rakhmawati (Departemen Manajemen, 2022)
The purpose of this study is to investigate the mediating effect of affective commitment in relationship between supportive work environment and employee retention. This research conducted at Kyriad Muraya Hotel Aceh with 92 employees as samples. The research method uses saturated samples and data collection is done through questionnaires. The data analysis technique used is multiple linear regression analysis. The findings suggest that supportive work environment plays a crucial role in predicting the employee retention. affective commitment partially mediates the relationship between supportive work environment and employee retention.